2020
DOI: 10.1177/1060028020983323
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity on Tranexamic Acid Efficacy in Adult Patients With Major Bleeding

Abstract: Background: Tranexamic acid (TXA) is an antifibrinolytic used for prophylaxis and treatment of acute bleeding. Although fixed dosing is often used in practice, weight-based dosing is sometimes used in the operating room (OR). The efficacy and safety of fixed-dose TXA is not well established in patients with above average weight or body mass index. Objective: To characterize the efficacy and safety of intravenous TXA in obese patients with major bleeding. Methods: This was a retrospective review of 165 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“… 63 They found that there were no differences in blood product administration or other secondary clinical outcomes between patients <100 kg or ≥100 kg who received fixed‐dose TXA. 63 Taken together, it likely remains appropriate to give fixed‐dose TXA for indications other than surgical‐related bleeding.…”
Section: Txa Dosing and Administration Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“… 63 They found that there were no differences in blood product administration or other secondary clinical outcomes between patients <100 kg or ≥100 kg who received fixed‐dose TXA. 63 Taken together, it likely remains appropriate to give fixed‐dose TXA for indications other than surgical‐related bleeding.…”
Section: Txa Dosing and Administration Considerationsmentioning
confidence: 99%
“…Franz et al sought to address this gap by collecting data on 165 patients who received fixed‐dose TXA for non‐operative indications (≈20% with trauma listed as bleed type) 63 . They found that there were no differences in blood product administration or other secondary clinical outcomes between patients <100 kg or ≥100 kg who received fixed‐dose TXA 63 . Taken together, it likely remains appropriate to give fixed‐dose TXA for indications other than surgical‐related bleeding.…”
Section: Txa Dosing and Administration Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postpartum hemorrhage, characterized by rapid and substantial blood loss, can lead to a sudden decrease in blood volume, resulting in acidosis and deterioration of maternal coagulation function, and possibly leading to hemor-rhagic shock [1]. Moreover, cesarean section procedures themselves can induce changes in hemorheology and increase coagulation factors and platelet activity, predisposing pregnant women to thrombosis after delivery and posing serious risks to maternal safety [2]. Therefore, prompt intervention is crucial to restore coagulation function.…”
Section: Introductionmentioning
confidence: 99%